Celiac disease: histology-differential diagnosis-complications. A practical approach: Review - Villanacci, Vincenzo; Vanoli, Alessandro; Leoncini, Giuseppe; Arpa, Giovanni; Salviato, Tiziana; Reggiani Bonetti, Luca; Baronchelli, Carla; Saragoni, Luca; Parente, Paola (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Celiac disease is a multi-factorial chronic inflammatory intestinal disease, characterized by malabsorption resulting from mucosal injury after ingestion of wheat gluten or related rye and barley proteins. Inappropriate T-cell-mediated immune response against ingested gluten in genetically predisposed people, leads to characteristic histological lesions, as villous atrophy and intraepithelial lymphocytosis. Nevertheless, celiac disease is a comprehensive diagnosis with clinical, serological and genetic characteristics integrated with histological features. Biopsy of duodenal mucosa remains the gold standard in the diagnosis of celiac disease with the recognition of the spectrum of histological changes and classification of mucosa damage based on updated Corazza-Villanacci system. Appropriate differential diagnosis evaluation and clinical context also for the diagnosis of complications is, moreover, needed for correct histological features interpretation and clinical management.